2011
DOI: 10.2527/jas.2010-3335
|View full text |Cite
|
Sign up to set email alerts
|

Dietary vitamin E and lipid and color stability of beef and pork: Modeling of relationships1

Abstract: Dietary vitamin E supplementation provides a feasible option to extend the shelf life of meat. However, the costs of extra supplementation necessitate an accurate level of feeding to achieve the maximum return in product quality improvement. The current study aimed to quantify the effects of total dietary vitamin E intake on muscle α-tocopherol concentration in cattle and pigs, and to relate muscle α-tocopherol concentration to lipid oxidation and color of meat. Through computerized and manual searches, 13 stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 74 publications
3
19
1
1
Order By: Relevance
“…In the light of the results found for the antioxidant status parameters measured in muscle, it can be stated that, in the present study, the positive effect of DCP on the resistance of muscle lipids to oxidation could be explained by the higher deposition of α-tocopherol in muscle from the animals fed the CIT diet compared with the CON treatment. Indeed, it has been widely demonstrated that the concentration of vitamin E in muscle plays a major role in protecting lipids from oxidation and some authors were able to develop models to predict the development of lipid oxidation in meat based on the levels of vitamin E in muscle (Sales and Koukolová, 2011). In the present study, we found no correlation between the α-tocopherol content in the muscle and the TBARS value at the start of the incubation in the presence of Fe/Asc catalyst, whereas a negative correlation was evident with the TBARS values measured after 30 min (−0.61; P < 0.01) and 60 min (−0.55; P = 0.01).…”
Section: +2mentioning
confidence: 99%
“…In the light of the results found for the antioxidant status parameters measured in muscle, it can be stated that, in the present study, the positive effect of DCP on the resistance of muscle lipids to oxidation could be explained by the higher deposition of α-tocopherol in muscle from the animals fed the CIT diet compared with the CON treatment. Indeed, it has been widely demonstrated that the concentration of vitamin E in muscle plays a major role in protecting lipids from oxidation and some authors were able to develop models to predict the development of lipid oxidation in meat based on the levels of vitamin E in muscle (Sales and Koukolová, 2011). In the present study, we found no correlation between the α-tocopherol content in the muscle and the TBARS value at the start of the incubation in the presence of Fe/Asc catalyst, whereas a negative correlation was evident with the TBARS values measured after 30 min (−0.61; P < 0.01) and 60 min (−0.55; P = 0.01).…”
Section: +2mentioning
confidence: 99%
“…Deterioration of these qualities can result in substantial economic losses (Sales and Koukolova, 2011). Meat color is the most important factor in determining consumer preference when buying meat products, especially that of red meats such as beef.…”
Section: Introductionmentioning
confidence: 99%
“…The meat quality preservative properties of vitamin E have been thoroughly investigated and it has been well established that α-tocopherol is the most potent form of natural vitamin E for these purposes (Sales and Koukolova, 2011). Mitsumoto et al (1993) revealed that dietary supplementation with vitamin E is more effective at extending the shelf-life of meat than postmortem treatment of the meat.…”
Section: Introductionmentioning
confidence: 99%
“…Although the effect of dietary vit. E on lipid oxidation and discoloration in meat was assessed in different ways [11] [12] [13], its preventive effect was much less studied on PUFA rich meats except in one study on calf muscles using very low amount of synthetic vitamin E (4 g/animal/d) [14]. Nevertheless, high vit.…”
Section: Introductionmentioning
confidence: 99%